STUDI KOMPARATIF TENTANG KARAKTER PEDULI SOSIAL PADA MAHASISWA YANG DONOR DARAH DAN TIDAK DONOR DARAH DI UNIVERSITAS RIAU - Dewi, Merita; Gimin, Gimin; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research was conducted with the aim to determine the level of participant social care character in students who are blood donors donors at University of Riau, the social care character in students who are not blood donors at the Universiy of Riau and to know the level of differences of social care character in students who are blood donors and not blood donors at the University of Riau. The population in this study amounted to 34.398 people with the sample in this study amounted to 100 people namely blood donors 50 people and not blood donors 50 people sampling using random sampling technique. Technique of data collection is observation, questionnaire, interview and documentation with method uses quantitative descriptive and analyzed using data descriptive analysis and different test two separate samples by SPSS version 21. The results show that the answer is that the social care level of student who are blood donors is very this higt is proven to be as much as 82,2% while the social care level of student who are not blood donors is very higt too is proven to be as much as 79,16%. And the results are based on SPSS version 21 that there is no difference in social care character of students who are blood donors and not blood donors. As evidenced by sgi > 5% (0,152 > 0,5) and t count 1,942 smaller than t table 1,98447.Key Words: Comparative, Social Care